Modelo analítico para ecossistemas estaduais de inovação - Bassalo, Gisa Helena Melo (Universidade Federal de São Carlos, 2017)
In the recent global scenario, innovation has become strategic for the competitiveness of organizations, regions and countries. It is very difficult to predict or even plan for innovation that has a strong impact on markets, economies and people's lives, but it is possible to plan and focus efforts to strengthen the environment necessary for its emergence. Improving this environment is increasingly related to the ability of these regions and countries to promote innovation. According to critics, the current analytical frameworks for systemic approaches to innovation are not able to provide all the information needed to formulate public policy, or at least struggle to demonstrate how they translate their analytical results into policy prescriptions. In addition, despite their efforts, the most important tools for measuring the ability of territories to innovate are appropriate to the reality of developed economies but are not able to measure the real (innovative) potential of developing or underdeveloped economies. This work proposes to define an operational analytical model to capture the reality of Brazilian innovation ecosystems in terms of their ability to favor innovation. To achieve these objectives, the methodological strategy was carried out in four steps: a systematic review of the literature on innovation policies, indicators and systems; mapping of the characteristics present in this material to construct an analytical schema (set of characteristics and their metrics); validation of the schema through factorial analysis techniques and measuring the innovative performance of ecosystems, and finally; a typology proposal for innovation ecosystems, through cluster analysis techniques, and identification of their potentialities and weaknesses. As a result, we obtained the following: appropriate macro-dimensions, dimensions and indicators to capture the relevant characteristics of innovation state ecosystems; performance measurements of these ecosystems in relation to innovation; a typology for ecosystems according to the macro-dimensions that interfere with their capacity to favor innovation; and the potentialities and weaknesses of the ecosystems of twenty-six states and the Federal District in Brazil through the application of the model. The main scientific and socioeconomic contributions were: generation of knowledge about the Brazilian innovation state ecosystems; an alternative proposal for the operational detailing of analysis and monitoring activities for the operation of these ecosystems; support for future improvement, problem minimization and/or functional actions; a typology to enable the identification of potentialities and weaknesses, and; a proposal for analytical characteristics appropriate to the scale of research in and the socioeconomic condition of developing countries.
Analytic model for states innovation ecosystems
Keywords: Ecossistema de inovação; Política de inovação; Sistema regional de inovação; Modelo de análise; Ecosistema de innovación; Política de innovación; Sistema regional de innovación; Innovation ecosystem; Innovation policy; Regional innovation system; Analytic model; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA